Development Of Creative Thinking In Junior Schoolchildren - Gulmira Jumaniyazovna Arslanova (Euro Asian Journal Publishing, 2023)
This article substantiates the idea of the relevance of developing creative thinking in junior schoolchildren, analyzes the use of various approaches and methods by primary school teachers. The author outlines views on the effectiveness of developing creativity in children in connection with the development in students of the ability to analyze, find patterns between objects and phenomena and create new non-standard ways to solve various educational and life problems.
Keywords: modernization; creativity; educational process; creative teacher